2017
DOI: 10.1186/s40634-017-0113-5
|View full text |Cite
|
Sign up to set email alerts
|

The use of lumbar epidural injection of platelet lysate for treatment of radicular pain

Abstract: BackgroundEpidural steroid injections (ESI) are the most common pain management procedure performed in the US, however evidence of efficacy is limited. In addition, there is early evidence that the high dose of corticosteroids used can have systemic side effects. We describe the results of a case series evaluating the use of platelet lysate (PL) epidural injections for the treatment of lumbar radicular pain as an alternative to corticosteroids.MethodsRegistry data was obtained for patients (N = 470) treated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
53
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(56 citation statements)
references
References 65 publications
(82 reference statements)
1
53
0
Order By: Relevance
“…The 10 patients in the study reported good results at their 3‐month follow‐up, suggesting that PRP may be a good alternative to epidural steroids and surgery 38 . Centeno et al reviewed the use of epidural platelet lysate injections as an alternative to corticosteroid injections for the treatment of lumbar radicular pain and found significant pain reduction and functional improvement throughout the 2‐year follow‐up period 39 . They concluded that platelet lysate injections have the potential to be a promising substitute for corticosteroid injections.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The 10 patients in the study reported good results at their 3‐month follow‐up, suggesting that PRP may be a good alternative to epidural steroids and surgery 38 . Centeno et al reviewed the use of epidural platelet lysate injections as an alternative to corticosteroid injections for the treatment of lumbar radicular pain and found significant pain reduction and functional improvement throughout the 2‐year follow‐up period 39 . They concluded that platelet lysate injections have the potential to be a promising substitute for corticosteroid injections.…”
Section: Discussionmentioning
confidence: 97%
“…This study could be the first RCT‐designed study to investigate the efficacy of caudal epidural LR‐PRP for patients with degenerative spinal pain. PRP and its derivatives have been used for various other epidural administrations (eg, autologous conditioned serum and platelet lysate preparations) 38–40 . Bhatia et al investigated the efficacy of PRP in patients with chronic prolapsed intervertebral discs.…”
Section: Discussionmentioning
confidence: 99%
“…Platelet‐based therapies have been used for almost 50 years since platelet rich plasma (PRP) was first developed (Andia & Abate, 2013). A huge number of commercial enterprises have arisen that each market PRP products to treat a spectrum of human medical conditions ranging from osteoarthritis to central nervous system pain management (Centeno et al., 2017; Le et al., 2018). The use of PRP has a number of disadvantages, most based on the notion that preparations containing platelets may induce aggregation and potentially occlude blood vessels (Wybier, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Pain reduction in both the ACS and steroid control groups was observed, with more sustained pain relief in the ACS group. 63 Two other prospective studies currently exist, with a registry of 470 patients treated with platelet lysate (PL) by Centeno et al 64 being the largest and observing significant numeric pain score changes through all time points compared to baseline. While there were no serious adverse events reported, 6.3% reported mild adverse events related to the treatment.…”
Section: Epidural Orthobiologic Studiesmentioning
confidence: 99%